2006
DOI: 10.1111/j.0014-3820.2006.tb01846.x
|View full text |Cite
|
Sign up to set email alerts
|

Parents Benefit From Eating Offspring: Density-Dependent Egg Survivorship Compensates for Filial Cannibalism

Abstract: Abstract. Why should animals knowingly consume their own young? It is difficult to imagine many circumstances in which eating one's own young (i.e., filial cannibalism) actually increases an individual's fitness; however, filial cannibalism commonly co-occurs with parental care in fishes. The evolutionary significance of filial cannibalism remains unclear. The most commonly accepted explanation is that filial cannibalism is a mechanism by which caring males gain energy or nutrients that they reinvest into futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 23 publications
0
56
0
Order By: Relevance
“…As larger females are more fecund, density-dependent competition or survival is expected to be most important for offspring of larger females [29]. Although density-dependent egg mortality has been shown to occur in nests of sand gobies [43], little is known about possibility of density-dependent survival or competition for space among siblings in livebearers, as density-dependent processes are very difficult to study prior to birth. Again, more research is needed to determine the contribution of within-brood density-dependence to observed variation in swordtail offspring sizes.…”
Section: Discussionmentioning
confidence: 99%
“…As larger females are more fecund, density-dependent competition or survival is expected to be most important for offspring of larger females [29]. Although density-dependent egg mortality has been shown to occur in nests of sand gobies [43], little is known about possibility of density-dependent survival or competition for space among siblings in livebearers, as density-dependent processes are very difficult to study prior to birth. Again, more research is needed to determine the contribution of within-brood density-dependence to observed variation in swordtail offspring sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Klug et al (2006) found that simulated partial-clutch cannibalism increased survivorship of the remaining sand goby eggs, presumably because of densitydependent egg survival. Furthermore, a mathematical model suggests that the evolution of filial cannibalism can be facilitated by selective consumption of lower-quality eggs (Klug and Bonsall 2007).…”
Section: Discussionmentioning
confidence: 96%
“…; Manica ), but this pattern is clearly not universal (e.g., Lindström and Sargent ; Klug and St Mary ; Klug et al. ). Other ideas such as selective cannibalism of inferior eggs (Klug and Lindström ) or a reduction of egg density to enhance oxygen availability to the remaining eggs (Payne et al.…”
Section: Introductionmentioning
confidence: 99%